SCOPE OF MEDICINE BIOINORGANIC CHEMISTRY, HYDRO AND MATERIALS SCIENCE - Beyer, L. (1998)
The Bioinorganic Chemistry is the newest discipline of Inorganic Chemistry. Despite his youth, has found many applications in various fields such as medicine, Hidrometalugia and Materials Science. in this article an overview of the current status of research in this area is presented through concrete examples of the principles and applications as the study of biominerals, biomineralization processes, bioceramic, bioleaching and metal complexes for medicinal use (therapeutic and diagnostic). The objective of this work is reaslatar the importance of this emerging discipline and integration possibilities it offers for the Peruvian and Latin American science.